2017
DOI: 10.1266/ggs.17-00046
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sigma factor-mediated cell surface stress responses in <i>Bacillus</i> <i>subtilis</i>

Abstract: Proteins belonging to the sigma factor family in eubacteria initiate transcription by associating with RNA polymerase. A subfamily, the extracytoplasmic function (ECF) sigma factors, which form a widely distributed bacterial signal transduction system comprising a sigma factor and a cognate membrane-embedded antisigma factor, regulates genes in response to stressors that threaten cell envelope integrity including the cell wall and membrane. The Gram-positive soil bacterium Bacillus subtilis provides a valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…In B. subtilis , one of its three DACs monitors the integrity of chromosomal DNA and serves as a checkpoint for the cells entering the sporulation process. c‐di‐AMP‐specific phosphodiesterases (CDAs, containing either GGDEF‐DHHA‐DHHA1 or HD‐type domains) hydrolyse c‐di‐AMP. Most, albeit not all of them do not contain any sensor domains and apparently simply reverse the effects of DACs. ECF sigma factors comprise a vast signal transduction machinery that regulates transcription primarily in response to intracellular cues but can also respond to environmental factors, such as envelope stress (Helmann, ; Asai, ), blue light (Gaidenko et al ., ) or extracellular polysaccharides (Kahel‐Raifer et al ., ; Yaniv et al ., ; see Mascher, ; Paget, ; Sineva et al ., for reviews). Signal transduction from Ser/Thr/Tyr protein kinases (STYKs) involves direct or indirect phosphorylation of various (mostly unknown) targets. The few experimentally characterized targets of Ser/Thr/Tyr protein phosphorylation include metabolic (e.g.…”
Section: Distribution Of Environmental Sensors In Selected Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…In B. subtilis , one of its three DACs monitors the integrity of chromosomal DNA and serves as a checkpoint for the cells entering the sporulation process. c‐di‐AMP‐specific phosphodiesterases (CDAs, containing either GGDEF‐DHHA‐DHHA1 or HD‐type domains) hydrolyse c‐di‐AMP. Most, albeit not all of them do not contain any sensor domains and apparently simply reverse the effects of DACs. ECF sigma factors comprise a vast signal transduction machinery that regulates transcription primarily in response to intracellular cues but can also respond to environmental factors, such as envelope stress (Helmann, ; Asai, ), blue light (Gaidenko et al ., ) or extracellular polysaccharides (Kahel‐Raifer et al ., ; Yaniv et al ., ; see Mascher, ; Paget, ; Sineva et al ., for reviews). Signal transduction from Ser/Thr/Tyr protein kinases (STYKs) involves direct or indirect phosphorylation of various (mostly unknown) targets. The few experimentally characterized targets of Ser/Thr/Tyr protein phosphorylation include metabolic (e.g.…”
Section: Distribution Of Environmental Sensors In Selected Bacteriamentioning
confidence: 99%
“…• Diadenylate cyclases (DACs, containing the conserved the DisA_N domain) produce second messenger c-di-AMP. Cyclic di-AMP has been shown to mediate signalling related to K + ion transport, osmotic pressure inside the cell and cell wall stress (Corrigan and Gründling, 2013;Gründling and Lee, 2016;Commichau et al, 2015;2018). In B. subtilis, one of its three DACs monitors the integrity of chromosomal DNA and serves as a checkpoint for the cells entering the sporulation process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of BcrC is primarily controlled by the extracytoplasmic function sigma factor M (14,30). While the physiological input triggering activation of M still remains elusive (31,32), the broad range of inducing conditions, including cell wall antibiotics, salt, ethanol, and others, suggests that it is not a specific chemical compound but rather a cellular cue upon cell envelope damage that activates the M response (33). Interestingly, despite the seemingly unrelated input stimuli for the BceAB and the BcrC resistance modules-with BceAB being activated by a "drugsensing" mechanism (antibiotic flux) and BcrC by a "damage-sensing" mechanismprevious work revealed that there is a high level of interdependency between the modules (26).…”
mentioning
confidence: 99%
“…Expression of BcrC is primarily controlled by the extracytoplasmic function sigma factor σ M (14, 31). While the physiological input triggering activation of σ M still remains elusive (32, 33), the broad range of inducing conditions, including cell wall antibiotics, salt, ethanol and others, suggests that it is not a specific chemical compound but rather a cellular cue upon cell envelope damage that activates the σ M response (34). Interestingly, despite the seemingly unrelated input stimuli for the BceAB and the BcrC resistance modules – with BceAB being activated by a “drug-sensing” mechanism (=antibiotic flux) and BcrC by a “damage-sensing” mechanism – previous work revealed that there is a high level of inter-dependency between the modules (27).…”
Section: Introductionmentioning
confidence: 99%